Análise longitudinal na gestão da Polícia Militar do Estado do Espírito Santo - Pereira, José Dirceu (2009)
This study is about an empirical research, accomplished with a group of managers of higher hierarchy of the Military Police of Espírito Santo, that sought to analyze the change in the management of the organization at two specific historical moments: duri